Assistance for Families with Stunting Children in the Kebon Bawang Health Center Assistance Area - Kusumaningsih, Indriati; Anjela, Novi; Novelina, Novelina (AMK : Abdi Masyarakat UIKA, 2024)
Stunting is a condition of impaired growth and development in toddlers due to long-term malnutrition, repeated exposure to infection, and lack of stimulation. Stunting is influenced by the health status of adolescents, pregnant women, toddlers' eating patterns, as well as economic, cultural, and environmental factors such as sanitation and access to health services. Stunting conditions in early life have an impact on growth disorders so that they can have functional consequences that can be detrimental to children. Some of these consequences include low cognitive and learning abilities, low income as adults, low productivity and, when accompanied by excessive weight gain in childhood, an increased risk of chronic diseases related to nutrition in adulthood. Information from the Head of Kebon Bawang Health Center, there are 15 families who have children with stunting. In an effort to handle the case, IPKKI DKI Jakarta designed a Family Assistance activity with Stunting Children in the Kebon Bawang Health Center Assistance Area involving the STIK Sint Carolus. STIK Sint Carolus will send companions by involving lecturers and students in the field of community nursing in handling cases of families with stunted children. With direct assistance from health workers for families with stunted children, the level of family independence and knowledge will increase and children with stunting will receive treatment in the Kebon Bawang sub-district area. This activity is important to increase parental awareness in improving children's health.